Progress toward restoring the Everglades : the third biennial review, 2010 (National Academies Press, 2010)
"Although the progress of environmental restoration projects in the Florida Everglades remains slow overall, there have been improvements in the pace of restoration and in the relationship between the federal and state partners during the last two years. However, the importance of several challenges related to water quantity and quality have become clear, highlighting the difficulty in achieving restoration goals for all ecosystem components in all portions of the Everglades. Progress Toward Restoring the Everglades explores these challenges. The book stresses that rigorous scientific analyses of the tradeoffs between water quality and quantity and between the hydrologic requirements of Everglades features and species are needed to inform future prioritization and funding decisions."--Publisher's description
Keywords: Wetland restoration -- Florida -- Everglades.; Restoration ecology -- Florida -- Everglades.; Wetland management -- Florida -- Everglades.; Everglades (Fla.) -- Environmental conditions.; Zones humides -- Réhabilitation -- Floride -- Everglades.; Réhabilitation (Écologie) -- Floride -- Everglades.; Zones humides -- Gestion -- Floride -- Everglades.; Everglades (Flor.) -- Conditions environnementales.; NATURE -- Environmental Conservation & Protection.; Ecology; Restoration ecology; Wetland management; Wetland restoration; Florida -- Everglades